Efficacy and Safety of Subacromial Corticosteroid Injection in Type 2 Diabetic Patients. (20th September 2018) - Blonna, Davide; Bonasia, Davide Edoardo; Mattei, Lorenzo; Bellato, Enrico; Greco, Valentina; Rossi, Roberto
Abstract : Purpose . In type 2 diabetic patients affected by chronic shoulder pain, subacromial injection with corticosteroid could be an effective treatment. The aim of this study was to measure the risk-benefit ratio of this treatment. Methods . Twenty patients with well-controlled diabetes were included in a prospective study. In a first preinjection phase, patients were asked to measure glycemia for 7 days, before breakfast and dinner, and then 2 hours after lunch and dinner. Baseline data including Constant Score (CS), Subjective Shoulder Value (SSV), and Numerical Rating Scale (NRS) for pain were collected. Patients were treated with subacromial injection with 40 mg of Methylprednisolone Acetate and 2 ml of Lidocaine. At discharge, patients were asked to remeasure glycemia for the following week. Results . The overall pain improved and patients graded their shoulder as "greatly improved". At 30-day follow-up, the SSV and the CS improved, considering pain but not ROM. The average daily glycemia was 136 mg/dl before injection, 161 mg/dl the day of the injection (p<0.001), and 170 mg/dl one day after injection (p<0.001). Glycemia was not statistically different 3 days after injection. Conclusion . Subacromial injection is an effective short-term treatment in type 2 diabetic patients affected by shoulder pain, but a closed follow-up is recommended in all these patients. This trial is registered withNCT03652480 . The Protocol ID is SHOULDERDM2013.